La realidad virtual como estrategia interactiva y de exploración en el aprendizaje de Biología Humana con estudiantes del sexto semestre de la Carrera Pedagogía de las Ciencias Experimentales: Química y Biología, periodo mayo 2021 – octubre 2021 - Pumarica Berrones, Pablo Andres (2022)
The present research work was carried out at the National University of Chimborazo in the Faculty of Education, Human Sciences and Technology, During the last years in our country the educational system has been subject to changes in order to improve the quality of education with the insertion of technological elements that promote real experiences and activities that focus on a deeper and interactive learning. However, even teachers who teach Human Biology resort to theoretical classes using slides, videos and images to teach these contents, generating a certain filtering of what their learning implies, and it has also been observed that the most used strategy is the expository class through PowerPoint presentations. Therefore, the objective was: "To propose virtual reality as an interactive and exploratory strategy in the learning of Human Biology". The research design was non-experimental, with a qualitative, bibliographic and field approach. For data collection, a survey was used, which was directed to the study population, constituted by 13 sixth semester students of the Pedagogy of Experimental Sciences: Chemistry and Biology, period May 2021 - October 2021. After analyzing the data, it became evident that 77% of the students totally agree that it is important to apply Virtual Reality simulators in the teaching-learning process and it is concluded that its application favors the students' learning by increasing the levels of acquisition and retention of knowledge, and also awakens and promotes greater interest and attention, encouraging active learning.